Prevalence of Oral Exostoses in Northern China During the Past Six Millennia—From a Sex and Age Perspective. Issue 2 (25th March 2023) - Lu, Mengting; Kang, Ting; Kong, Yujia; Chen, Xuepeng; Shao, Jinling
Abstract : This study is intended to investigate oral exostoses of 5 sample populations, spanning over 6000 years, from the same region of Northern China, to determine the significance of sex and age on the development of oral exostoses during each time period. The samples analyzed were 306 dry jaws from human skeletons, which were excavated from 4 archeological sites: Banpo (6700–5600 y BP), Shaolingyuan (3000 y BP), Shanren (2200 y BP), and Chang'an (1000–1300 y BP), as well as the modern Xi'an district. The sex and the age of the samples at death were estimated. The degree of buccal exostosis (BE), torus mandibularis (TM), and torus palatinus (TP) and the TP shape were recorded. The results showed BEs in the Banpo and Chang'an regions, TMs in the Banpo region were more often diagnosed in males than in females. Conversely, females in Shaolingyuan showed a higher prevalence and severity of TM than that in males. The occurrence of BEs in the Shanren and Xi'an regions, TMs in the Banpo, Chang'an, and Xi'an regions, as well as TPs in the Banpo region significantly increased with age at death. In conclusion, sex differences and increasing trends with age in relation to oral exostoses were found in samples from Northern China during the past six millennia.